Dystocia Due to Breech Presentation of a Dicephalic Fetal monster in A Buffalo: Breech Presentation and Dicephalic Fetal monsterosity in A Buffalo - Dutt, Ravi; Dalal, Jasmer; Ravish, Sukhbir; Pradeep; Anupama; Yadav, Ritu; Rashmi; Hitesh (Animal Reproduction Update, 2022)
A case of dystocia due to breech presentation coupled with bilateral hip flexion (breech presentation) in a dicephalic foetal monster having bilateral brachygnathism in a Murrah buffalo was brought to Veterinary Clinical Complex (VCC) of the university which was relieved through obstetrical maneuvers per-vaginally, is reported here.
Keywords: Breech presentation; Dicephalic; Dystocia; Foetal monster; Mutation